Oral manifestations of type 2 diabetes mellitus patients attending The Alberto Sabogal Hospital - Vega NM, Linares (2017)
Objective: To determine the most frequent oral manifestations of type 2 diabetes mellitus patients at the Sabogal Hospital during 2016. Methods: Descriptive, cross-sectional study. 47 patients were evaluated with an age range of <40 years, 40-65 years and > = 65 years and in the female / male ratio was 1/1, with type 2 diabetes mellitus from the Sabogal Hospital during October, 2016. Data were collected with a chart that included socio-demographic variables of the patients and oral cavity examinations. The statistical analysis was frequency distribution and association of variables with chi-square analysis. Results: The most frequent age group was, patients over 65 years of age (48.94%). Arterial hypertension was the most frequent comorbidity with 57.45% and retinopathy as a chronic complication with 42.55%. From the sample 63.83% were insulin-dependent. The most frequent oral manifestation was partial edentulism with 85.11%, followed by caries with 82.98%, 78.72% gingivitis,